Quality assessment of smoked catfishes (Clarias gariepinus, Heterobranchus longifilis and Synodontis clarias) from selected fish markets in Benue State, Nigeria - Fanyam, Umawam Samuel; Kwaghvihi, Orfega Benjamin; Annune, Paul Aunde (Universitas Malikussaleh, 2024)
The quality assessment of smoked catfish from selected fish markets in Benue state was carried out. Clarias gariepinus, Heterobranchus spp. and Synodontis spp. each weighing 500g were collected from Abinsi and Wadata markets. The proximate composition, mineral composition and organoleptic assessment were carried out. Association of Official Analytical Chemists (AOAC) methods were adopted for the determination of proximate and mineral composition while a 9-point Hedonic scale ranging from 1(dislike extremely) to 9(like extremely) was a procedure for organoleptic quality determination. Results for proximate and mineral compositions showed good standard but varied from market to market. Abinsi fish markets showed that Heterobranchus spp. had 10.16%, 12.74%, 58.98%, 16.42%, 1.71%. Clarias gariepinus had 9.09%, 10.10%, 66.11%, 13.94%, 0.76%. Synodontis spp. had 8.19%, 11.07%, 55.80%, 22.68%, and 2.27% as values for moisture content, ash content, protein content, lipid content and carbohydrates content while Wadata fish market Heterobranchus spp. had 10.34%, 11.89%, 59.48%, 15.71%, and 2.59%. Clarias gariepinus had 8.88%, 11.37%, 68.97%, 10.37%, 0.38%. Synodontis spp. had 8.36%, 12.19%, 56.35%, 21.30%, and 1.81% for moisture content, ash content, protein content, lipid content and carbohydrates content respectively. The mineral composition for Abinsi fish showed that Heterobranchus spp. had 240.33 mg/100g, 395.48 mg/100g, 32.44 mg/100g, 0.03 mg/100g, 0.80 mg/100g, 5.37 mg/100g; Clarias gariepinus had 270.30 mg/100g, 278.05 mg/100g, 32.14 mg/100g, 0.21 mg/100g, 0.30 mg/100g, 5.06 mg/100g; Synodontis spp. had 330.05 mg/100g, 257.78 mg/100g, 34.24 mg/100g, 0.24 mg/100g, 0.40 mg/100g, 6.98 mg/100g; for Potassium, Calcium, Sodium, Copper, Zinc and Iron while in Wadata fish market Heterobranchus spp. had 250.30 mg/100g, 127.88 mg/100g, 39.84 mg/100g, 0.39 mg/100g, 0.68 mg/100g, 4.95 mg/100g; Clarias gariepinus had 410.15 mg/100g, 159.33 mg/100g, 33.03 mg/100g, 0.22 mg/100g, 0.60 mg/100g, 5.96 mg/100g; Synodontis spp. had 300.45 mg/100g, 295.48 mg/100g, 33.93 mg/100g, 0.30 mg/100g, 0.71 mg/100g, 12.0 mg/100g; for Potassium, Calcium, Sodium, Copper, Zinc and Iron. The sensory evaluation revealed that taste, appearance, texture and odour were accepted by the panellist and significant difference occurred (P<0.05) among samples from both markets. The three catfish species from this study were found to be rich in protein content, Potassium, Calcium, and Sodium with low presence of Copper, Zinc, Iron, lipid and carbohydrate contents.Keywords: Catfishes; markets; quality assessment; smoked